Diagnóstico de parvovirus canino en la ciudad de Pasaje por la prueba de Elisa - Arias Torres, Andrea Fernanda (2010)
This investigation was made in Pasaje city, province El Oro, during the months of June to August of the 2009, with the following goals: 1) to diagnose the canine Parvovirus in the Pasaje city for ELISA'S test, 2) to determine the prevalence according to race, age, sex and origin of the infected animals. The number of investigated animals was 100, all presented compatible symptoms of gastrointestinal illness with canine Parvovirus. We use the test of diagnose quick of canine Parvovirus and Coronavirus and the results were written in registration leaves that contained the following information: race, age, sex and origin. It was obtained a prevalence of 37% as a result, with a predilection of infection for the animals younger than 5 months.